From Judith to Mary: An Exploration of the Role of Women in Salvation History - Marchelino Joshua (MELINTAS An International Journal of Philosophy and Religion, 2024)
In the Scriptures, Judith emerges as a prominent heroine of Israel, demonstrating her strength and intelligence to liberate her people from the grasp of oppression. On the other hand, Mary, Jesus’ mother, is revered as the Mother of God, who, through profound humility and obedience, embraces her pivotal role in the narrative of humanity’s redemption. This article aims to explore the significant parallels between these two remarkable figures, highlighting how they embody feminine qualities such as courage, intelligence, fidelity, and humility. These traits enable them to serve as divine instruments in the fulfillment of God’s salvific plan. Utilizing exegetical methods and theological reflections, the author emphasizes how Judith and Mary exemplify an active essence of femininity that transcends the patriarchal limitations traditionally placed on women’s roles in religious narratives. Both figures are positioned not merely as recipients of salvation but as active agents engaging in the divine work of salvation. This analysis can provide fresh insights into the contributions of women throughout the history of salvation and underscores their relevance in the ongoing struggles for liberation in contemporary contexts.